New sources of resistance to Septoria tritici blotch in wheat seedlings - Simón, María Rosa (2016)
The resistance of a set of Argentine wheat cultivars, differentials, and foreign lines with known genes of resistance to Zymoseptoria tritici was assessed at the seedling stage against a set of molecularly characterized Argentine fungal isolates under three experimental conditions. The experimental design was a split-splitplot with two replications. The environment conditions were the main plots, the fungal isolates were the subplots and the wheat lines with known resistance genes or used as differential lines or the Argentine commercial cultivars were the sub-subplots. Sixteen fungal isolates were inoculated on 23 wheat accessions including 12 foreign lines with known resistance genes, two differential lines, and nine Argentine cultivars that were selected on the basis of their moderate resistance to natural infection, to identify isolate-specific and partial resistances. The genotypes TE 9111 and Oasis among the foreign lines along with the Argentine cultivars Pro INTA Puntal, Klein Volcán and Buck 75 Aniversario expressed the highest number of specific-resistance interactions. Flame, Tadinia and Kavkaz among the foreign lines showed partial resistances to a higher number of fungal isolates; a comparable resistance pattern was also obtained in the Argentine cultivars Klein Sagitario, Klein Dragón, Don Ernesto and Buck Arriero. Our study demonstrated that the presence of resistance genes in several foreign lines against Septoria tritici blotch is effective against some of the Argentine fungal isolates. In addition, the Argentinean wheat cultivars that showed isolate-specific and nonspecific resistances probably carry novel resistance genes against the pathogen.